Efektivitas Metode Edukasi Audiovisual terhadap Self Management pada Pasien Hipertensi - Fernalia Fernalia; Busjra Busjra; Wati Jumaiyah (Jurnal Keperawatan Silampari, 2019)
This study aims to determine the effectiveness of audiovisual education methods on self management in hypertensive patients. This study used a quasi-experimental design with a non-equivalent control group pre and post test design, with a total sample of 38 respondents consisting of an intervention group and a control group. Obtained a significant difference in the average self-management of the intervention group after the audiovisual education method was performed with (p = 0,000). There was no relationship between age (p = 0.71), sex (p = 0.955) and self-management in hypertensive patients. While self management will increase after the audiovisual education method is carried out and controlled by knowledge (p = 0.005). The conclusion of this study is the audiovisual education method can improve self management in hypertensive patients. Keywords: Audiovisual Education, Hypertension, Self Management